Ancient Art in the Collection of the National Museum in Gdańsk - Grzegorz First (Studies in Ancient Art and Civilization, 2024)
Among the Polish collections of antiquities, a lesser-known set of ancient artifacts is housed in the National Museum in Gdańsk. This collection includes Egyptian, Etruscan, Roman, and Coptic artifacts of uncertain provenance and acquisition history. The only definite aspect is the acquisition of some items: Coptic fabrics from the collection of Robert Forrer—a Swiss collector, antiquarian, archaeologist, and art historian. The remaining artifacts stored in Gdańsk have not been thoroughly studied; they do not form a homogeneous collection, and it cannot be ruled out that they may also be remnants of former bourgeois collections dating back to the 16th century or German collections acquired in Gdańsk after World War II.